Can the Concentration of Citric Acid Affect Its Cytotoxicity and Antimicrobial Activity? - Luciano Giardino; Luigi Generali; Paolo Savadori; Mirela Cesar Barros; Leticia Lobo de Melo Simas; Jolanta Pytko-Polończyk; Wojciech Wilkoński; Vasudev Ballal; Flaviana Bombarda de Andrade (MDPI AG, 2022)
Background: There has been no unanimity concerning the ideal concentration of citric acid for safe use in clinical practice. This study evaluated the cytotoxicity and the antibacterial activity in infected dentinal tubules of 10% and 1% citric acid (CA) solutions. Methods: The cytotoxicity of CA solutions in DMEM (diluted 1/10, 1/100) was assessed in L-929 fibroblasts. A broth macrodilution method (MIC and MBC) was used to assess CA antibacterial concentration. The antimicrobial activity of CA solutions was also evaluated after their final rinse inside root canals in previously Enterococcus faecalis-contaminated dentinal tubules. Ten infected dentine samples were rinsed for 5 min with 5% NaOCl and subsequently with 1% citric acid for 3 min. Another 10 were rinsed with 5% NaOCl and 10% citric acid for 3 min; the remaining four specimens were utilized as positive controls. Two uncontaminated specimens were used as negative controls. After LIVE/DEAD BacLight staining, the samples were assessed using CLSM to analyze the percentage of residual live and dead cells. Results: Both undiluted and diluted CA solutions showed severe toxicity; no changes from normal morphology were displayed when diluted 1/100. The MIC and MBC of CA were 6.25 mg/mL and 12.50 mg/mL, respectively. CA solutions demonstrated significantly low levels of bacterial counts than the positive control group, reporting a value of 9.3% for the 10% solution versus the 1% solution (35.2%). Conclusions: Despite its valuable antimicrobial properties, the cytotoxic effects of citric acid should be considered during endodontic treatment.